2020
DOI: 10.21776/ub.ijabs.2020.28.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Does Corporate Governance Predict Firm Profitability? an Empirical Study in Oman

Abstract: Purpose — This research aims to test whether corporate governance (CG) predicts firm profitability in a sample of firms listed in the financial mark in Oman. Design/methodology/approach — This research analyses cross-sectional data across 50 non-financial firms. This study used annual reports for the fiscal year 2018 to analyze the impact of CG on firm profitability. This work tested its hypotheses and analyzing them via the Partial Least Squares (PLS). Findings — The result of this research indicates that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 19 publications
0
17
1
Order By: Relevance
“…(Hoes and Gehlert, 2020) believe that the three-lines-of-defence model of compliance environment and culture within organizations can prevent major scandals. Corporate governance mechanisms in Oman are not as effective as in more developed countries and that therefore regulators in such a less developed country should impose and encourage substantial corporate governance practices instead of merely adhering to pro-forma practices (Ahmed et al , 2020; Baatwah et al , 2015). International Accounting Standards (IAS) are applicable to the Oman business environment (Ojha and Kashoob, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Hoes and Gehlert, 2020) believe that the three-lines-of-defence model of compliance environment and culture within organizations can prevent major scandals. Corporate governance mechanisms in Oman are not as effective as in more developed countries and that therefore regulators in such a less developed country should impose and encourage substantial corporate governance practices instead of merely adhering to pro-forma practices (Ahmed et al , 2020; Baatwah et al , 2015). International Accounting Standards (IAS) are applicable to the Oman business environment (Ojha and Kashoob, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is to be noted that CG system deals with the setup tools that the forms, actions and activities are managed, to maximizing principal value via the duty of directors and enhance firm's performance (Ahmed, Alabdullah, Shaharudin, & Putri, 2020;Alabdullah, 2018). Ahmed, Alabdullah, Thottoli, and Maryanti (2020) in their study focused on testing the relation between CG tools and firms' performance in GCC companies. This study indicated that a positive relation among all predictors is found: ownership, board size, audit commission, gender and firm financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CG in GCC is one of the oldest and most successful experiences in the Arab world (Ahmed, Alabdullah, Thottoli, & Maryanti, 2020). Also, it is one of the basics of monitoring the path of companies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful implantation of complete functional (ICT enabled) software application boosts students' skills and knowledge and finally encourages the successful building of knowledge over the process of entrepreneurial innovation. Students from various disciplines showed higher confidence levels on ICT-enabled financial statements to prepare and compare CVP analysis and breakeven analysis (Banerjee et al, 2018;Ahmed et al, 2020;Alabdullah et al, 2019). Business start-ups used CVP ignorantly and have suggested that ICT-enabled CVP analysis, breakeven analysis and such other accounting tools to be introduced among young aspirant entrepreneurs so that improve productivity (Abdullahi et al, 2017).…”
Section: Proficiency In Preparing Cost Volume Profit Analysismentioning
confidence: 99%